Hubungan Rating Bintang Terhadap Peran Akuntansi Manajemen Strategis (Studi Empiris Pada Perusahaan Hotel di Sumatera Selatan) - Antonius Singgih Setiawan; Rahmawati Rahmawati (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to test whether the star rating as parameter of level hotel tobring a better impact on the implementation of strategic management accounting role inthe management of the hotel business. Using a sample of 66 respondents General Manager/Leader of Hotel in the province of South Sumatra (resepon rate 88%), research hypotheses were tested using regression analysis. The results showed that the star ratinghotel a positive impact on the implementation of strategic management accounting role infunctional role of accounting and the use of strategic management accounting techniques.